Antifungal Production of a Strain of Actinomycetes spp Isolated from the Rhizosphere of Cajuput Plant: Selection and Detection of Exhibiting Activity Against Tested Fungi - A. Alimuddin; Jaka Widada; Widya Asmara; M. Mustofa (Indonesian Journal of Biotechnology, 2011)
Actinomycetes are bacteria known to constitute a large part of the rhizosphere microbiota. Their isolation is an important step for screening of new bioactive compounds. Culturable actinomycetes populations from cajuput plant rhizosphere soils in Wanagama I Forest UGM Yogyakarta were collected to study about their antifungal activity. Among 17 of a total 43 isolates that showed activity were screened for producing antifungi substances. Screening for antifungal activity of isolates were performed with dual culture bioassay in vitro. One isolate that was designated as Streptomyces sp.GMR-22 was the strongest against all tested fungi and appeared promising for a sources of antifungal. Culture’s supernatant and mycelia were extracted with chloroform, ethyl acetate and methanol, respectively. Antifungal activity of crude extracts was tested by diffusion method against tested fungi. The result indicates that isolates of actinomycetes from cajuput plant rhizosphere could be an interesting sources of antifungal bioactive substances.